Celastrol Attenuates the Invasion and Migration and Augments the Anticancer Effects of Bortezomib in a Xenograft Mouse Model of Multiple Myeloma - Shanmugam, Muthu K.; Ahn, Kwang S.; Lee, Jong H.; Kannaiyan, Radhamani; Mustafa, Nurulhuda; Manu, Kanjoormana A.; Siveen, Kodappully S.; Sethi, Gautam; Chng, Wee J.; Kumar, Alan P. (Frontiers in Pharmacology, 2018)
Several lines of evidence have demonstrated that deregulated activation of NF-B plays a pivotal role in the initiation and progression of a variety of cancers including multiple myeloma (MM). Therefore, novel molecules that can effectively suppress deregulated NF-kB upregulation can potentially reduce MM growth. In this study, the effect of celastrol (CSL) on patient derived CD138+ MM cell proliferation, apoptosis, cell invasion and migration was investigated. In addition, we studied whether CSL can potentiate the apoptotic effect of bortezomib, a proteasome inhibitor in MM cells and in a xenograft mouse model. We found that CSL significantly reduced cell proliferation and synergistically enhanced apoptosis when used in combination with bortezomib and upregulated caspase-3 in these cells. CSL also inhibited invasion and migration of MM cells through the suppression of constitutive NF-kB activation and expression of downstream gene products such as CXCR4 and MMP9. Moreover, CSL when administered either alone or in combination with bortezomib synergistically inhibited MM tumor growth and decreased serum IL-6 and TNF-a levels. Overall, our results suggest that CSL can abrogate MM growth both in vitro and in vivo and may serve as a useful pharmacological agent for the treatment of myeloma and other hematological malignancies.